2012
DOI: 10.1242/dev.076299
|View full text |Cite
|
Sign up to set email alerts
|

COUP-TFII is essential for metanephric mesenchyme formation and kidney precursor cell survival

Abstract: SUMMARYDevelopment of the metanephric kidney in mammals requires complex reciprocal tissue interactions between the ureteric epithelium and the mesenchyme. It is believed that Gdnf, produced in the metanephric mesenchyme, activates Ret signaling in the Wolffian duct to initiate the formation of the metanephros. However, the molecular mechanism for induction of Gdnf in the metanephric mesenchyme is not completely defined. Previous studies demonstrated that during the early stages of kidney development, loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 43 publications
(49 reference statements)
1
36
0
Order By: Relevance
“…Furthermore, GST pull-down analysis reveals that COUP-TFI and Sp1 physically interact in vitro [100]. Accumulating evidence supports that COUP-TFs activate gene expression through tethering to the Sp1 transcription factor, which binds at the Sp1 site of the target genes, such as Otx2 in the eye [16, 19, 20, 24, 27, 36, 71, 73, 100102] (Fig 1B; Table 2). Consistent with this conclusion, chromatin immunoprecipitation assay (ChIP) indicates that COUP-TF is recruited to the Sp1 site and knockdown of Sp1 or mutation of the Sp1 binding site eliminates the recruitment of COUP-TF to the Sp1 site [16, 71, 73, 100]…”
Section: Coup-tf Genes Proteins and Molecular Mechanisms Of Actionmentioning
confidence: 99%
“…Furthermore, GST pull-down analysis reveals that COUP-TFI and Sp1 physically interact in vitro [100]. Accumulating evidence supports that COUP-TFs activate gene expression through tethering to the Sp1 transcription factor, which binds at the Sp1 site of the target genes, such as Otx2 in the eye [16, 19, 20, 24, 27, 36, 71, 73, 100102] (Fig 1B; Table 2). Consistent with this conclusion, chromatin immunoprecipitation assay (ChIP) indicates that COUP-TF is recruited to the Sp1 site and knockdown of Sp1 or mutation of the Sp1 binding site eliminates the recruitment of COUP-TF to the Sp1 site [16, 71, 73, 100]…”
Section: Coup-tf Genes Proteins and Molecular Mechanisms Of Actionmentioning
confidence: 99%
“…For example, COUP-TFβ is known to be required for heart development, temporal specification of neural stem cells, kidney precursor cell survival and male fertility in mammals Naka et al, 2008;Qin et al, 2008;Yu et al, 2012). In adult tilapia, COUP-TFβ-A was preferentially expressed in the brain, heart, kidney and testis, while its paralog, COUP-TFβ-B, was not or very weakly expressed in all of the 8 tissues examined.…”
Section: Expression Divergence Of Duplicated Genesmentioning
confidence: 99%
“…Survival analysis showed that the methylation level of the SIX2 gene is significantly associated with clinical outcome for WT, suggesting that measurement of methylated SIX2 promoter DNA in tissue may contribute to improved estimation of the postoperative survival chances of these patients. Critical upstream activators of SIX2, such as EYA1, HOXA11, HOXD11, Wnt9b, and PAX2, are known to play a regulatory role during the expression process [36][37][38]. However, the mechanisms and specific roles of these genes in the initiation and development of WT are currently unknown.…”
Section: Discussionmentioning
confidence: 99%